Understanding probiotics' role in allergic children: the clue of gut microbiota profiling. Issue 5 (October 2015) - Vernocchi, Pamela; Del Chierico, Federica; Fiocchi, Alessandro G.; Hachem, May El; Dallapiccola, Bruno; Rossi, Paolo; Putignani, Lorenza
Abstract : Purpose of review: To investigate the functional role of gut microbiota in diet-modulated diseases, evaluating probiotic administration effects by systems biology-driven approaches. Understanding the role of host–gut microbial and gut microbe–microbe interactions in either allergic and healthy children may assist in selecting effective and targeted probiotics for personalized therapies. Recent findings: Food allergy shows a significant increase, especially in Western countries where growing epidemiological data indicate prevalence of small family groups, limited rate of infections in childhood compared with low-income countries, high consumption of sterile foods, hence stimulating a poor trigger of the gut immune system. Therefore, new therapeutic strategies to treat food allergy consist of probiotic administration since early life, thus modulating gut microbiota through immune system stimulation at the mucosal level. Summary: Currently, new insights for probiotic selection should take into consideration both phenotyping and genotyping bacterial features and host–microbial cross-talk at gut level, by employing multicomponent systems biology approaches to unveil gut ecosystem dynamics in terms of bacteria phylotypes and their metabolic activities. Moreover, new food processes need to be considered to assess the actual performance of probiotic strains administered to allergic patients. The advent of high-performance platforms employing genomic- and mass spectrometry-based techniques has opened new perspectives on the gut microbiota field, and may now serve as advanced tool to dynamically investigate the interplay between probiotics and gut microbiota ecology under allergic conditions.